Response of Several Sugar Cane Varieties to Infection by Fusarium sacchari, the Cause of Pokkah Boeng Disease in Greenhouses - Asniah Asniah; Muhammad Botek; Mawar Safitri; Fransiskus Ganti; Agustono Slamet; Dewi Nurhayati Yusuf (Jurnal Ilmiah Membangun Desa dan Pertanian, 2026)
The fungus Fusarium sacchari causes pokkah boeng, a sugarcane disease that frequently occurs in sugarcane plantations. The purpose of this study is to evaluate how different sugarcane plant varieties respond to F. sacchari infection, which causes Pokkah boeng disease in greenhouses. This study was conducted in the Plant Protection Laboratory and the Land Greenhouse of Halu Oleo University's Faculty of Agriculture in Kendari. A Completely Randomized Design (CRD) was employed in the study, with four treatments that were repeated five times. Each treatment included six plant units, totaling 120 polybags. Incubation period, disease incidence, disease severity, AUDPC, and durability category were the characteristics that were noted. The result of this research indicates that the V1 treatment (Kidang Kencana of variations) has the longest incubation period (up to 14 days), a disease incidence of 56.73%, and a disease severity of 22%. The kidang kencana variety also shows that the rate of development of pokkah boeng disease every week is slower, but the level of resistance category is susceptible.